2015
DOI: 10.2151/sola.2015-005
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Lightning Jumps Associated with a Tornadic Supercell on 2 September 2013

Abstract: Cloud-to-ground (CG) and total (both CG and intracloud) lightning trends were investigated in a tornado-producing (F2) supercell thunderstorm that occurred over the Kanto Plain in Japan on 2 September 2013. The spatiotemporal signatures of mesocyclone (MC) and storm development were also analyzed using Doppler radar data. The results revealed that rapid increases of lightning flash rates ("lightning jumps") occurred in CG and total flash rates 0−7 and 0−14 min before tornadogenesis, respectively, which are sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The fourth case was a tornadic supercell thunderstorm (T4) observed on 2 September 2013 (Figs. 2j, k, l), and the associated tornado occurred in Saitama and Chiba prefectures after 14:00 JST (Suzuki et al 2014;Nishihashi et al 2015). The analysis period was from the initiation to the eve of tornado formation.…”
Section: Overview Of the Four Thunderstormsmentioning
confidence: 99%
“…The fourth case was a tornadic supercell thunderstorm (T4) observed on 2 September 2013 (Figs. 2j, k, l), and the associated tornado occurred in Saitama and Chiba prefectures after 14:00 JST (Suzuki et al 2014;Nishihashi et al 2015). The analysis period was from the initiation to the eve of tornado formation.…”
Section: Overview Of the Four Thunderstormsmentioning
confidence: 99%
“…An F2 (Fujita scale) tornado‐bearing storm caused severe wind damage in and around Koshigaya City from 0450 to 0520 UTC on 2 September 2013 (Nishihashi et al, ). Studies (Nishihashi et al, ; Sakurai et al, ) have analysed observational data and have characterized the relationship between storm evolution and lightning activity. In this study, we focussed on the predictability of the storm.…”
Section: Methodsmentioning
confidence: 99%
“…Our method employed high‐temporal‐resolution (1 min) scanning data and we could, therefore, investigate the sensitivity of the results to the temporal resolution of radar scanning. Furthermore, we evaluated the assimilation impact on rainfall and vertical vorticity forecasts during a tornadic thunderstorm over Koshigaya City, Japan, on 2 September 2013 (Nishihashi et al, ; Sakurai et al, ). Finally, we discuss the utility and limitation of TRAF.…”
Section: Introductionmentioning
confidence: 99%
“…Very interestingly, a Figure (4c) was presented of compiled CG and IC/CG positive lightning flash locations centered on the same US tornado incidence and severe storm coverages shown here in Figures 1 and 2. Very recently, Nishihashi et al [60] have reported on both CG and IC lightning activity in connection with tornadogenesis occurring on 2 September 2013 on the Kanto Plain in Japan. Their measurements included observations made by the (Japan) Lightning Detection Network (LIDEN), coupled with radar reflectivity and Doppler velocity data.…”
Section: Ic Lightning and Tornadogenesismentioning
confidence: 99%